Emotional Intelligence of SMA N 2 Padang Students and Implications in Guidance and Counseling Services - Maya Nurva Novita; Zikra Zikra (Universitas Negeri Padang, 2021)
Emotional intelligence is the ability to recognize, process, and control emotions so that individuals are able to respond positively to any conditions that stimulate the emergence of various emotions. This research is motivated by the phenomenon of students who have low emotional intelligence. This study aims to describe how the general description of students' emotional intelligence is seen from the aspects of recognizing one's emotions, managing emotions, motivating oneself, recognizing other people's emotions, and building relationships. This research uses descriptive quantitative research. The population in this study were all students of SMA N 2 Padang, totaling 1,038 students and the sample in this study was 321 students. Sampling in this study using stratified random sampling technique. The instrument used in this study was a questionnaire about emotional intelligence with a Likert scale model. The data analysis technique used descriptive statistical techniques. This study describes the emotional intelligence of SMA N 2 Padang students based on the following aspects: (1) recognizing self-emotions in the low category with a percentage (55%), (2) managing emotions in the medium category with a percentage (69%), (3) motivating self is in the low category with a percentage (49%), (4) recognizing the emotions of others is in the medium category with a percentage (66%), and building relationships is in the medium category with a percentage (68%).